Up right, not right up: Primacy of verticality in both language and movement - Boulenger, Véronique; Finos, Livio; Koun, Eric; Salemme, Roméo; Desoche, Clément; Roy, Alice C. (Frontiers in Human Neuroscience, 2022)
When describing motion along both the horizontal and vertical axes, languages from different families express the elements encoding verticality before those coding for horizontality (e.g. going up right instead of right up). In light of the motor grounding of language, the present study investigated whether the prevalence of verticality in path expression also governs the trajectory of arm biological movements. Using a 3D virtual-reality setting, we tracked the kinematics of hand pointing movements in five spatial directions, two of which implied the vertical and horizontal vectors equally (i.e. up right +45° and bottom right -45°). Movement onset could be prompted by visual or auditory verbal cues, the latter being canonical (“en haut à droite” / up right) or not (“à droite en haut” / right up) in French. In two experiments, analyses of the index finger kinematics revealed a significant effect of gravity, with earlier acceleration, velocity and deceleration peaks for upward (+45°) than downward (-45°) movements, irrespective of the instructions. Remarkably, confirming the linguistic observations, we found that vertical kinematic parameters occurred earlier than horizontal ones for upward movements, both for visual and congruent verbal cues. Non-canonical verbal instructions significantly affected this temporal dynamic: for upward movements, the horizontal and vertical components temporally aligned, while they reversed for downward movements where the kinematics of the vertical axis was delayed with respect to that of the horizontal one. This temporal dynamic is so deeply anchored that non-canonical verbal instructions allowed for horizontality to precede verticality only for movements that do not fight against gravity. Altogether, our findings provide new insights into the embodiment of language by revealing that linguistic path may reflect the organization of biological movements, giving priority to the vertical axis.